Commemorating Anniversaries of the Life and Work of Francysk Skaryna in Lithuania from the Viewpoint of Book Studies and Scholarly Communication - Navickienė, Aušra (Knygotyra, 2023)
The aim of this article is to reconstruct the history of how anniversaries of Francysk Skaryna’s life and work were commemorated in the Lithuanian academic environment. It looks for answers to questions of when these anniversaries began to be celebrated in Lithuania, which part of the academic community was involved in these activities, and how they have contributed to the dissemination of the knowledge of book studies. The author analysed scholarly events and anniversary publications dedicated to Francysk Skaryna by discussing the authors and the content of scholarly publishing results, as well as the organizers, topics, and participant geography of scholarly events. Collection of data from written sources, such as various bibliographic resources, official documents, memoirs, and informational articles published in periodicals in various historical periods, was aided by examining informational and scholarly publications de visu and applying other methods of historical research. The collected historical facts were studied in the context of Skaryna studies and the historiography of the Lithuanian book, evaluated from the viewpoint of scholarly communication and systematized by using the already-established periodization of Lithuanian book studies.